The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fendo.2021.812385
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol-Mediated Hypercalcemia, Somatostatin Receptors Expression and 25-Hydroxyvitamin D3-1α- Hydroxylase in GIST Tumors

Abstract: Hypercalcemia is a common complication in cancer patients Mainly caused by Parathyroid hormone-related protein (PTHrP) secretion and metastasis. Calcitriol secretion is a rare source of hypercalcemia in solid tumors, especially in gastrointestinal stromal tumors (GIST). We present a case report of a female patient with a 23 cm gastric GIST that expressed somatostatin-receptors and presented with severe hypercalcemia due to calcitriol secretion. Calcium control was achieved with medical treatment before the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The underlying mechanisms driving hypercalcaemia in these patients with GIST were identified in six of the previous documented cases. Interestingly, four patients were found to have raised calcitriol levels (1,25(OH)2-vitamin D 3 ) 21 23 25 26. Vitamin D levels were noted to be insufficient in our case.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The underlying mechanisms driving hypercalcaemia in these patients with GIST were identified in six of the previous documented cases. Interestingly, four patients were found to have raised calcitriol levels (1,25(OH)2-vitamin D 3 ) 21 23 25 26. Vitamin D levels were noted to be insufficient in our case.…”
Section: Discussionmentioning
confidence: 53%
“…Conversely, hypercalcaemia resulting from overproduction of calcitriol in solid tumours is very rare and the mechanism remains unclear 27. However, molecular analysis of tumour cells from a patient with GIST presented by Herrera-Martinez et al demonstrated mRNA expression of 1α-hydroxylase and vitamin D receptors in GIST tumour cells, confounding the proposed mechanism of calcitriol-mediated hypercalcaemia in patients with GIST 26. Identifying this underlying aetiology of hypercalcaemia in patients with GIST is imperative for future management, as recent data have suggested patients with calcitriol elevation are less likely to respond to antiresorptive therapy than patients without calcitriol elevation 27…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of 1,25(OH)2D accounts for approximately 1% of cases of HM [ 1 ]. It is primarily associated with hematologic malignancies such as Hodgkin and non-Hodgkin lymphoma but has also been reported in some solid tumors such as ovarian dysgerminoma, gastrointestinal stromal tumor (GIST), and seminomas [ 1 , 5 ]. Here, we present a patient with abdominal liposarcoma and HM caused by the production of 1,25(OH)2D.…”
Section: Introductionmentioning
confidence: 99%